Productivity dispersion and sectoral labour shares in Europe - Martina Lawless; Luke Rehill (The Economic and Social Research Institute (ESRI), 2020)
The stability of the labour share of income is a fundamental feature of macroeconomic models, with broad implications for the shape of the production function, inequality, and macroeconomic dynamics. However, empirically, this share has been slowly declining in many countries for several decades, though its causes are subject of much debate. This paper analyses the drivers of labour share developments in Europe at a sectoral level. We begin with a simple shift-share analysis which demonstrates that the decline across countries has been primarily driven by changes within industries. We then use aggregated microdata from CompNet to analyse drivers of sector-level labour shares and to decompose their effects into shifts in the sector average or reallocation of resources between firms. Our main findings are that the advance of globalisation and the widening productivity gap between "the best and the rest" have negative implications for the labour share. We also find that most of the changes are due to reallocation within sectors providing support for the "superstar firms" hypothesis. The finding that globalisation has had a negative impact on the labour share is of relevance for policy in the context of the current backlash against globalisation and reinforces the need to ensure benefits of globalisation and productivity are passed on to workers.
Keywords: 330; Lohnquote; Branche; Dekompositionsverfahren; Globalisierung; Produktivität; OECD-Staaten